2017
DOI: 10.4103/1119-3077.181318
|View full text |Cite
|
Sign up to set email alerts
|

Parental beliefs and practices regarding childhood fever in Turkish primary care

Abstract: We conclude that parents share important misconceptions about definition, treatment, and consequences of childhood fever and tend to treat fever before seeking medical care with a substantial rate of wrong doses and wrong intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…E Yavuz et al in their study found that more than 80% of the parents did not know the correct temperature for fever for the measured site. There are similar previous reports in Turkey and culturally diverse populations in different countries [16][17][18][19][20]. Concerning when to give a child treatment, 36% of the participants would give treatment at 37 °C.…”
Section: Resultssupporting
confidence: 85%
“…E Yavuz et al in their study found that more than 80% of the parents did not know the correct temperature for fever for the measured site. There are similar previous reports in Turkey and culturally diverse populations in different countries [16][17][18][19][20]. Concerning when to give a child treatment, 36% of the participants would give treatment at 37 °C.…”
Section: Resultssupporting
confidence: 85%
“…6 Considering the practice of assessing fever, study in Turkey showed that 45.8% measured temperature with thermometer which is consistent with current finding as 42% confirm fever by using thermometer. 12 Similarly, 82.4% assess the temperature by touching with hand is shown in study conducted in Ghana which supports the result of our survey as 87% assess temperature by touching with hand. 10 Study in Morocco showed that 85.9% used paracetamol during fever which supports the results in which 82.4% of respondents used paracetamol.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in a newly published study by Talebi et al .,[ 16 ] 67.4% of the mothers reported measuring the body temperature by touching the hand of the child, while 24.8% of the them used a thermometer. In a more recent published article in Turkey by Yavuz et al .,[ 20 ] 45.8% of parents measure fever with a thermometer prior and only 38% of them used the thermometer correctly.…”
Section: Discussionmentioning
confidence: 99%